Enantiopure Ferrocene‐Based Planar‐Chiral Iridacycles: Stereospecific Control of Iridium‐Centred Chirality. Issue 9 (25th January 2016) - Arthurs, Ross A.; Ismail, Muhammad; Prior, Christopher C.; Oganesyan, Vasily S.; Horton, Peter N.; Coles, Simon J.; Richards, Christopher J.
Abstract: Reaction of [IrCp*Cl2 ]2 with ferrocenylimines (Fc=NAr, Ar=Ph, p ‐MeOC6 H4 ) results in ferrocene C−H activation and the diastereoselective synthesis of half‐sandwich iridacycles of relative configuration S p *, R Ir *. Extension to ( S )‐2‐ferrocenyl‐4‐(1‐methylethyl)oxazoline gave highly diastereoselective control over the new elements of planar chirality and metal‐based pseudo‐tetrahedral chirality, to give both neutral and cationic half‐sandwich iridacycles of absolute configuration S c, S p, R Ir . Substitution reactions proceed with retention of configuration, with the planar chirality controlling the metal‐centred chirality through an iron–iridium interaction in the coordinatively unsaturated cationic intermediate. Abstract : Controlling chirality : The reaction of [IrCp*Cl2 ]2 with ( S )‐2‐ferrocenyl‐4‐(1‐methylethyl)oxazoline results in the diastereoselective synthesis of either cationic or neutral half‐sandwich iridacycles. Excellent control is achieved over the new elements of planar chirality and metal‐based pseudo‐tetrahedral chirality (see figure).